Molecular data suggest a multispecies complex of Phoxinus (Cyprinidae) in the Western Balkan Peninsula - Palandačić, Anja; Bravničar, Jernej; Zupančič, Primož; Šanda, Radek; Snoj, Aleš (Molecular phylogenetics and evolution, 2015)
This study aimed to evaluate the phylogeographic distribution of Phoxinus phoxinus sensu lato populations in the Balkan Peninsula using molecular methods. For the western Balkan Peninsula, two species (Danubian P. phoxinus and Adriatic P. lumaireul) have been suggested, but not confirmed by subsequent morphological studies or by genetic data. For the present study, more than 300 specimens were collected from the western Balkans. A partial sequence of the mt cyt b gene analysed using Bayesian and ML methods revealed several well-supported clades, with distances ranging from 4% to 11%. The clades were corroborated by RAG1 sequence analysis. Thus, the molecular analysis points to a multispecies complex of Phoxinus sp. with ranges of the clades extending north-west to south-east along the western Balkan Peninsula. In addition, the dispersion of fish through subterranean water connections in karst is indicated.
Keywords: Cyprinidae; fylogeografie; Balkan Peninsula; Sequence Analysis, DNA; Molecular methods; Bayesova věta; Genes, Mitochondrial; sekvenční analýza DNA; Western Balkan Peninsula; Animals; Bayes Theorem; mitochondriální geny; Phylogeography; zvířata; Balkánský poloostrov; Phoxinus